Strategi Pembelajaran Era Digital: Usulan Skenario dalam Menyambut Transformasi STAIN Purwokerto Sebagai Salah Satu PTAI yang Mengembangkan Cyber Campus - fajar hardoyono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The most important devices for digital campus development are computer network, Internet, and content. Computer network and Internet depend on the outside factors, i.e. vendors and technology suppliers. The last devices depend on the internal factor but it must be suitable by the users. The users in digital campus include all of the students, lectures, and the non-academic staff. This paper is not only to propose how to manage the content of digital learning but also to propose the digital learning model and the development of cyber campus in State College of Islamic Studies of Purwokerto, Central Java.